Enhancing the Value-Added of Pesticide-Free Riceberry for Promoting the Local Economy with the Paganyaw Community Identity of Ban Mae San, Mae Sam Sub-District, Si Satchanalai District, Sukhothai Province - Jarernpanit, Thannapat; Panpho, Phakakorn; Jarernsuk, Suppanit (Ratchaphruek Journal, 2024)
This study aims to enhance the value of pesticide-free riceberry cultivated by the Paganyaw community in Ban Mae San, located in the Mae Sam Subdistrict of Si Satchanalai District, Sukhothai Province. The focus is on developing riceberry products, with active participation from community members in designing packaging and product branding. The packaging design will highlight the unique identity and traditional wisdom of the Paganyaw community, emphasizing their expertise in rice terrace farming and their location in a fertile watershed area. Sharing the product’s story can enhance the value of the community’s riceberry. Additionally, the packaging has been designed to meet standard vacuum sealing requirements, while the branding reflects the unique identity of the area. The branding is beautiful, modern, and detailed, telling stories that convey messages from community members to consumers. Moreover, online sales channels are being developed with the involvement of both the community and local administrative organizations. Through this entire process, riceberry products can be transformed into community products originating from Ban Mae San and Mae Sam Subdistrict. This initiative not only boosts the economic income of the community but also provides a return on investment ratio of 50% within 4 months.